Vendor supplied MARC records for online collections - Sahadath, Catelynne (Henry Stewart Talks, 2015)
Encoding vs. Content standards, Information contained in MARC records, File extensions, MARC online, Record sets for large, online collections of content, Assessing & planning record loads using MarcEdit